Differentiable Preinvex and Prequasiinvex Functions - Huriye Kadakal (Universal Journal of Mathematics and Applications, 2020)
In this paper, a new identity for functions defined on an open invex subset of set of real numbers is established, and by using this identity and the Hölder and Power mean integral inequalities we present new integral inequalities for functions whose powers of derivatives in absolute value are preinvex and prequasiinvex. We should especially mention that the results obtained in special cases coincide with the well-known results in the literature.